Training Seminar cum workshop on Sampling ,statistics and standardization in chemical analysis and environmental management - Sampling ,statistics...; Gunawardhana,H.D (Colombo Institute of chemistry, 2005)
Training Seminar Jan.25 ,2005
Keywords: seminar reports,statistics